Effect of rainfall intensity on the selectivity of splashed particles in semi-arid soils - Majid Foroumadi; Ali Reza Vaezi; j. n (مهندسی منابع آب, 2020)
Particles which transfer is effected by raindrop splash depends on several factors, including soil type and rainfall intensity. Although information on the role of these two factors in splash erosion is available, but the selectivity of particles in splash erosion is unknown. This study was conducted to investigate the effects of splash erosion and selectivity of particles in different soils under the influence of rainfall intensity. For this purpose, experiments were carried out in three different soils (Loam, Clay loam, Sandy clay loam) on tree rainfall intensities (10, 20 and 30 mm.h-1) under a constant slope of 10 % in three replications, with a total of 27 units in the form of a completely randomized design was done. According to the results, the highest and lowest amount of splash erosion in the soil were clay loam (80.45 g.m-2.min-1) and sandy clay loam (62.19 g.m-2.min-1), respectively. With increasing rainfall intensity, the intensity of splash erosion increased. In general, the selectivity of particles in the splash erosion is affected by the soil texture rainfall intensity and the interaction between of them. Sand, silt and clay particles were 3.23%, 59.70% and 37.07% of the share of splash particles. In all textures (except the loam texture), the selectivity of the silt particles at different levels of the gradient was greater than the rest. In the loam soil, clay particles were more selective than silt particles, due to the low clay particles in the initial soil sample.